The challenges of patient and public involvement in medical technology and in-vitro diagnostic research. (1st July 2018) - Uchegbu, Ijeoma; Sato, Momoko; Allam, Alison; Buckle, Peter; Hanna, George
Abstract : Patient and public involvement (PPI) in research is defined as 'research being carried out "with" or "by" members of the public rather than "to", "about" or "for" them'. A knowledge transfer event (KTE) was planned to share the experience of organizations who carry out medical technology research. The KTE was attended by organizations with an interest in the effective application of PPI in health-care research, including organizations from academia, industry and charities. The aim was to share current PPI experience and to discuss the development of a PPI impact measurement framework to support future growth in PPI application within medical technology research.